Democracy and Bildung/Erziehung-Towards a Universal Theory of Education - Johannes Bellmann; Hanno Su (MDPI AG, 2016)
Dewey's Democracy and Education is re-read as an attempt to develop a universal theory of education that, on the one hand, gives the broadest, most general view on education and, on the other hand, contextualizes every observation by binding it to the assumed perspective. Dewey's broad concept of education encompasses two dimensions that in the German discourse are usually connected to the distinction of Erziehung and Bildung. In its first dimension, it avoids a widespread "scholastic" view of education by focusing not only on formal but also on informal education. In its second dimension, it also avoids a widespread individualistic view on education by referring not only to growth of the individual, but also to growth of the social setting (democracy) on the whole. This outlook allows for investigating and reflecting any subject matter with respect to its educational aspects-including the process of theorizing itself. This reflective turn of theorizing education has consequences for the understanding of education as an academic field. A universal theory of education is at odds both with a disciplinary approach and the idea of education as an applied field for foundational disciplines. At the same time, it has the potential to reconnect to both configurations of the academic field if these configurations are understood slightly different than today.